The emerging role of estrogen in B cell malignancies. Issue 3 (4th March 2017) - Ladikou, Eleni-Eirini; Kassi, Eva
Abstract: Increasing evidence implicates a role of estrogens in hematological malignancies. We reviewed current knowledge on the emerging role of estrogens and estrogen receptors in normal B-cell function, chronic lymphocytic leukemia, and B-cell lymphoma. Data support that (1) normal human peripheral blood cells (mononuclear cells, total lymphocytes, T as well as B lymphocytes, and NK cells) express both estrogen receptor subtypes (ERα and ERβ), (2) B-cell malignancies express mainly ERβ while selective ERβ agonists inhibit cell growth and induce apoptosis, (3) estrogens regulate, via an ER-mediated pathway, gene expression of cyclins, kinases, bcl-2 proto-oncogene, activation-induced deaminase (AID), and transcription factors, associated with changes in BCR signaling and B cell tumorigenesis. In conclusion, estrogen receptors play an important role in normal B-cell function and B-cell tumorigenesis; however, further investigations are required to delineate the role of estrogens and estrogen receptors in the etiopathogenesis and therapy of B-cell malignancies.